Integrating Spirituality into the Evaluation Framework of Islamic Religious Education - Decky Saputra; Eva Latipah (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2024)
Learning evaluation is an essential component of the educational process, particularly in the context of Islamic Religious Education (IRE), which aims to nurture individuals who are religious and possess noble character. To date, the practice of evaluating IRE in many schools has largely focused on cognitive aspects, while the dimension of spirituality—the core of Islamic education—has often been overlooked. This study aims to examine the urgency and implementation of the spirituality dimension in the evaluation of IRE learning at primary schools in Bengkalis Regency. Employing a quantitative-descriptive approach, the study involved a population of IRE teachers from 30 public and private primary schools. A purposive sample of 60 teachers was selected. Data were collected through a closed-ended questionnaire based on a spirituality scale developed from the following indicators: awareness of God’s presence, sincerity, moral responsibility, and students’ inner transformation. The data were analyzed using descriptive statistics (percentages and means). The findings reveal that 82% of teachers acknowledge the importance of spiritual evaluation; however, only 41% consistently integrate it into their daily assessment practices. Most teachers (67%) admitted difficulties in measuring spiritual aspects objectively and systematically. Evaluation remains dominated by written tests and behavioral observations, with no explicit spiritual rubric. This study recommends the development of contextual spiritual evaluation instruments, teacher training in authentic spirituality-based assessment, and policy support from educational stakeholders to position the spirituality dimension as a central pillar of IRE evaluation. The study affirms that the success of IRE cannot be adequately measured by exam scores alone, but rather by the extent to which students experience genuine spiritual appreciation and transformation.